2015
DOI: 10.1002/eco.1696
|View full text |Cite
|
Sign up to set email alerts
|

Habitat connectivity as a metric for aquatic microhabitat quality: application to Chinook salmon spawning habitat

Abstract: Quality of fish habitat at the scale of a single fish, at the metre resolution, which we defined here as microhabitat, has been primarily evaluated on short reaches, and their results have been extended through long river segments with methods that do not account for connectivity, a measure of the spatial distribution of habitat patches. However, recent investigations of quality of aquatic habitat at the stream segment scale, at hundredth of metre resolution macrohabitat, indicate that the spatial distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 54 publications
(93 reference statements)
1
24
0
Order By: Relevance
“…Our results showed that habitat quality, characterized by surface water depth and velocity, is the primary predictor of site selection for salmonid spawning. This is in agreement with previous results on the importance of surface hydraulics and conditions that are used to quantify habitat quality [ Bjornn and Reiser , ; Bovee , ; Carnie et al ., ; Kondolf , ; Waddle , ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that habitat quality, characterized by surface water depth and velocity, is the primary predictor of site selection for salmonid spawning. This is in agreement with previous results on the importance of surface hydraulics and conditions that are used to quantify habitat quality [ Bjornn and Reiser , ; Bovee , ; Carnie et al ., ; Kondolf , ; Waddle , ].…”
Section: Discussionmentioning
confidence: 99%
“…We did not include substrate size in our analysis because median gravel size of 35 mm, suitable for spawning, is ubiquitous throughout the study reach [ McKean and Tonina , ]. We quantified the habitat quality from spatially distributed numerically predicted depths and velocities and univariate spawning habitat preference curves adopted from previous studies [ Bjornn and Reiser , ; Carnie et al ., ; Groves and Chandler , ; Hampton , ; Raleigh et al ., ; Smith , ; Tonina et al ., ].…”
Section: Methodsologymentioning
confidence: 99%
“…Previous research highlights the connection between channel morphology and topography and larger-scale sediment supply dynamics, such as those imposed by channel-hillslope coupling (Hoffman and Gabet, 2007;Hassan et al, 2019). Due to a limited number of long-term datasets, habitat modeling studies typically focus on short timescales or on spatial aspects of habitat (Harrison et al, 2011;Cienciala and Hassan, 2013;Hafs et al, 2014;Carnie et al, 2016), or examine conditions over longer timescales but assume static morphology (Fabris et al, 2017). Several flume-based and dam removal studies have noted that variations in sediment supply lead to changes in channel bed topography, such as bar building and erosion (Lisle et al, 1993;Dietrich et al, 2005;Venditti et al, 2012;Major et al, 2017) and pool filling (Hoffman and Gabet, 2007;Major et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With a few exceptions across limited spatial extents (McKean et al , ; Fonstad and Marcus, ; Carnie et al , ), none of these technologies can yet deliver the promise of a habitat census across the diversity of riverscapes occupied by salmonids (Bangen et al , ). While hybrid approaches combining multiple techniques have emerged as the most realistic way to obtain complete coverage of a portion of a riverscape (Legleiter, ; Javernick et al , ; Williams et al , ), for now, the notion of a physical habitat census is something we can only achieve across limited portions (albeit still impressive at 10–50 km) of rivers (Pasternack, ; Grams et al , ; Wyrick and Pasternack, ; Benjankar et al , ).…”
Section: Introductionmentioning
confidence: 99%